Percutaneous Transhepatic and Translumbar Sclerotherapy of a Thoracic Duct Cyst: A Case Report - Alrashidi, Ibrahim; Shin, Ji Hoon (The Arab Journal of Interventional Radiology, 2021)
A 58-year-old male presented with chronic abdominal pain lasting 5 years and a 15 × 6-cm multicystic thoracic duct cyst with three compartments, located in the right retrocrural and retrocardiac regions from T5/T6 to T12/L1. A transhepatic route was selected to sclerose the middle and lower compartments. Subsequent contrast injection showed minimal contrast passage into the upper compartment through a narrow neck, but the guidewire could not pass into this compartment. The contrast-filled upper compartment was punctured with a 22-g Chiba needle using a translumbar approach under cone-beam computed tomography (CT) guidance and ethanol sclerotherapy was performed. Six-month follow-up CT revealed decreased thoracic duct cyst size (5×3 cm) and no pain. This case illustrates successful percutaneous transhepatic and translumbar sclerotherapy for retrocardiac and retrocrural thoracic duct cysts, which are very difficult to remove surgically.
Keywords: sclerotherapy; thoracic duct cyst; ethanol; percutaneous